THE HEPATOTOXICITY EFFECT POST-CHEMOTHERAPY WITH GEMCITABINE-CARBOPLATIN REGIMEN: Efek Hepatotoksisitas Pasca Kemoterapi dengan Regimen Gemcitabine-Carboplatin - Annisa Diyan Meitasari; Jihan Nabila; Ulfa Afrinurfadhilah Darojati; M. Fiqry Zulpadly M H; Nindita Clourisa Amaris Susanto; Heru Sasongko; Diyah Tri Utami; Sholichah Rohmani; Anif Nur Artanti; Meta Kartika Untari; Dian Eka Ermawati (Universitas Airlangga, 2026)
Background: One of the main therapies for cancer is chemotherapy, however the administration is often accompanied by a wide range of Adverse Drug Reactions. Gemcitabine-carboplatin is one of the chemotherapy regimens frequently used in cancer treatment. Purpose: This study aims to determine the incidence, severity, and risk factors associated with the occurrence of hepatotoxicity after gemcitabine-carboplatin use. Methods: This study uses prospective observational research methods, including medical records and in-person interviews, with laboratory data (SGPT and SGOT) as the primary outcome. The sampling technique was purposive—the severity of hepatotoxicity was classified using the CTCAE instrument. The data obtained were then analyzed using bivariate and multivariate methods. Results: The incidence of ADRs was 16.66% in SGPT, with higher rates in grades 1 (14.44%) and 3 (2.22%). While the incidence of ADRs on SGOT increased by 22.22% across severity grades: 1 (15.56%), 2 (2.22%), and 3 (4.44%). Comorbidity is a significant risk factor for ADR incidence (p-value < 0.05). Conclusion: Patients with comorbidities had 8.076 times the tendency to experience ADRs as increased SGPT and 6.729 times the tendency to experience ADRs as increased SGOT. Results: The incidence of ADRs was 16.66% in SGPT increased with severity grade 1 (14.44%) and grade 3 (2.22%). While the incidence of ADRs on SGOT increased by 22.22% with severity grade 1 (15.56%), grade 2 (2.22%), and grade 3 (4.44%). Comorbidity is one of the risk factors that has a significant value on the incidence of ADRs with a p value <0.05. Conclusion: Patients with comorbidities had 8.076 times the tendency to experience ADRs in the form of increased SGPT and 6.729 times to experience ADRs in the form of increased SGOT.